Dosimetria experimental de modalidades de radioterapia de mama 3D-CRT, sIMRT e IMAT em fantoma de tórax - Elsa Bifano Pimenta (2019)
This study aims to investigate quantitatively and qualitatively the internal absorbed dose in radiotherapy breast cancer comparing a measured dose by radiochromic film with calculated dose by Treatment Planning System (TPS) at an anthropometric and anthropomorfic female thorax phantom. The thorax phantom was constructed and validated by the Núcleo de Radiações Ionizantes (NRI) UFMG research group. The phantom was elaborated by means of equivalent tissue materials with attenuation properties similar to human biological tissues. Materials such as elastin, vegetable oil and animal bone were used to mimic a skin, adipose tissue ribs and spine. The reproducibility of the radiation interaction phenomena with patient was the purpose of the NRI group simulator. The breast radiotherapy treatment planwas performed according toimages acquired at computed tomography (TC). Different techniques of radiotherapy were used, like follows: three-dimensional conformational RT (3DCRT), static intensity modulated radiotherapy (sIMRT) and intensity modulated arc therapy (IMAT) for this research. The treatment planning complexity and dose delivery capacity increases from 3DCRT to IMAT. The availability of such technologies vary between radiotherapy services. In the treatment planning process, the left breast was considered as planning target volume (PTV) and the lungs, heart and contralateral breast as organs at risk (OARs). The parameters for the calculation of the dose were not the same for all experiments due to the different modalities involved. The dosimetry was performed with the radiochromic films EBT2 and EBT3. The definition of the calibration curves was fundamental to correlate the absorbed dose with the intensity of the red component in the scanned films. Two-dimensional absolute dose distributions were obtained with the radiochromic films in each case. Through the two-dimensional dose maps, it was possible to identify high-dose regions (hot spots) and low dose (cold spots) in relation to the prescribed dose. Radiation internal transport phenomena contributing to the additional dose delivery were recorded in the radiochromic films. These results demonstrate the indispensability of radiochromic films and suggest the relevance of an anthropomorphic and anthropometric phantom in routine quality assurance (QA) in radiotherapy services. Therefore, it is clear the need to continue this research.